Adie pupil. Literature review - Judickaitė, A.; Zizas, A.; Varoniukaitė, A.; Šemeklis, L.; Glebauskienė, B. (Neurologijos seminarai, 2023)
Anisocoria (unequal pupil size) is a condition described as various lacerations in iris sphincter or dilator muscles, innervation abnormalities, or conditions caused by external pharmacological agents. Adie pupil is one of the causes of anisocoria. Adie pupil is a rare neurological disorder which represents itself with unilateral or bilateral mydriasis, unresponsiveness to bright or dim light, and constriction on accommodation. This condition is idiopathic, affecting 25-45-year-old adults, more frequently women. The symptoms are a unilateral or bilateral dilated pupil, photophobia, and blurred vision. The diagnosis is based on patients’ symptoms, clinical examination findings, and a dilute pilocarpine test can also be performed. Most patients do not need treatment. In this article, we review the epidemiology, pathogenesis, etiology, clinical evaluation, diagnostic features, treatment of Adie pupil, its relationship with COVID-19, and other conditions that cause anisocoria.